New coumarin−thiosemicarbazone based Zn(II), Ni(II) and Co(II) metal complexes: Investigation of cholinesterase, α‐amylase, and α‐glucosidase enzyme activities, and molecular docking studies - ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2023)
AbstractNew coumarin−thiosemicarbazone compounds and their zinc(II), nickel(II), and copper(II) metal complexes were synthesized and characterized. The inhibitory activities of these new coumarin−thiosemicarbazone‐based metal complexes against butyrylcholinesterase (BChE), acetylcholinesterase (AChE), α‐amylase, and α‐glucosidase were determined. The results showed that all the synthetic compounds exhibited potent inhibitory activities against all targets, as compared to the standard inhibitors, as revealed by the half‐maximal inhibitory concentration (IC50) and the inhibitory constant (Ki) values. The Ki values of the new complexes for BChE, AChE, and α‐glucosidase enzymes were obtained in the ranges of 115.84–276.07, 31.68–117.08, and 22.56–47.82 μM, respectively. Moreover, molecular docking studies provided support for the conclusion that coumarin−thiosemicarbazone zinc(II) (−102.34; −10.41 kcal/mol) and coumarin−thiosemicarbazone cobalt(II) complexes (−25.46; −9.49 kcal/mol) act as dual inhibitors for both AChE and α‐amylase species. Furthermore, coumarin−thiosemicarbazone cobalt(II) (−39.46 kcal/mol) and coumarin−thiosemicarbazone nickel(II) complexes (−39.41 kcal/mol) demonstrated potential as inhibitors of α‐glucosidase. Of all the compounds studied, bis‐3‐benzyl‐7,8‐dimethoxycoumarin−thiosemicarbazonato zinc(II) is the most potent drug against AChE.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; Kimya (çeşitli); Genel Kimya; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Multidisciplinary; Physical Sciences